2019
DOI: 10.1111/tbed.13176
|View full text |Cite
|
Sign up to set email alerts
|

Filarial worm circulation by mosquitoes along an urbanization gradient in southern Spain

Abstract: Mosquitoes are the main vectors of pathogens affecting wild animals, livestock and humans. Here, we used molecular tools to assess the local circulation of filarial parasites in mosquitoes collected during 2013 from natural, rural and urban habitats from southern Spain. We screened parasites in 22,791 female mosquitoes of the genera Aedes, Culex and Culiseta. Filarial worms were only detected in two mosquito pools. An Ae. caspius pool was positive for Setaria equina and an unidentified worm related to Onchocer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…pipiens and Cx. theileri as potential vectors was reported in two endemic regions of the Iberian Peninsula [148,149]. In Italy, several studies have continued to demonstrate the existence of culicid vectors of Dirofilaria in different regions of the country, such as Cx.…”
Section: Heartworm Vectorsmentioning
confidence: 99%
“…pipiens and Cx. theileri as potential vectors was reported in two endemic regions of the Iberian Peninsula [148,149]. In Italy, several studies have continued to demonstrate the existence of culicid vectors of Dirofilaria in different regions of the country, such as Cx.…”
Section: Heartworm Vectorsmentioning
confidence: 99%
“…The change of those two factors most likely contributed to the lack of infected pools detected in 2017 (Carlson et al 2015). The addition of CO 2 with BG Sentinel traps, as occurs in Europe (Schoener et al, 2017;Übleis et al, 2018;Martínez-de la Puente et al, 2019), may have enhanced the collection of Culex spp. in the study.…”
Section: Haemosporidamentioning
confidence: 99%
“…While these parasite-vector relationships may not be considered as important as those related to public health, there is a need to identify what other parasites are inhabiting the mosquito species within particular regions. As recent studies in Europe have reported, filarioid nematodes, known (Setaria sp) or unknown, are circulating in mosquitoes and wildlife in varied environments (Czajka et al, 2012;Kemenesi et al, 2015;Übleis et al, 2018;Martínez-de la Puente et al, 2019;Netherlands et al, 2020). Some may have an impact on the health of livestock or cervids while others may provide a means for an arbovirus to escape a midgut barrier and develop to infectious levels in the salivary glands (Vaughan et al, 2007;Vaughan and Turell, 2017).…”
Section: Haemosporidamentioning
confidence: 99%
See 1 more Smart Citation